Have Export Compositions Influenced the Economic Growth Among the European Union Countries in Central and Eastern Europe? - Tang, Donny (The European Journal of Applied Economics, 2020)
This study analyzes the export composition effects on the economic growth in the European Union (EU) countries in Central and Eastern Europe (CEE) during 1999-2016. The results confirm that the fuel and food exports have boosted growth after the EU accession. As expected, the agricultural exports have no effect on growth. Due to the different comparative advantages, the CEE countries have still relied on some raw material exports while developing manufactured exports. The results also indicate that the transportation equipment, textile, steel and chemical exports have accelerated growth. This can be attributed to the economies of scale in production given their greater access to EU markets.
Keywords: fuel; export; Europe; economic growth; composition